Design a current mode voltage reference - Peng, Haoxiang (2018)
The final report is for Final Year Project: Design a Current Mode Voltage Reference. Voltage reference is use to provide a voltage for out which is considered to have a very low dependence on the change of temperature, variation of power supply and some other process parameters. It is an important component in the analog signal system, and it has been widely used if many kinds of electrical devices in our daily life, because of its low dependence on temperature, low power consumption and so on. This project is to design a current mode bandgap voltage reference circuit so that it can generate a low voltage reference. And if we can use high order compensation in current mode, we will be able to make the current mode voltage reference be independent to temperature and even some other kind of variations. But in this experiment, only the temperature is going to be discussed. In the experiment, the BJT (Bipolar Junction Transistor) and the MOSFET (metal-oxidesemiconductor field-effect transistor) characterization and the temperature behaviour are going to be analysed and investigated. And the circuit will be designed under CSM (Charted Semiconductor Manufacturing) 0.18um CMOS process. Also, the student will be requited to design a suitable operational amplifier with a high output and gain which can be able to act like an ideal amplifier and make the voltage reference circuit works better. At last, all the simulation of the circuit will be performed by using Cadence program software which is provided by school lab. So, the Cadence tutorials need to be taken by student’s own to learn about how to use the simulation software efficiently